An update on tarsal coalitions. Issue 1 (February 2023) - Galea Wismayer, Martina; Brown, Rick
Abstract: Tarsal coalitions are anomalous connections between two or more bones in the hindfoot or midfoot secondary to embryonic failure of segmentation and differentiation of the mesenchyme. Calcaneonavicular and talocalcaneal coalitions are the most common. Although it is a congenital deformity, presentation is usually in adolescence which coincides with ossification of the coalition. Patients typically present with diffuse foot pain, calf muscle pain, recurrent ankle ligament sprains and a rigid hindfoot valgus deformity. Initial management is non-operative and may involve activity reduction, a trial of immobilization in a walking boot or cast, physiotherapy, corticosteroid injections and regular analgesia. Close to a third of patients experience symptom relief but the remaining patients with persistent symptoms will require operative intervention. Patients without degenerative joint disease undergo resection of the coalition. It is now established that an associated severe hindfoot valgus foot should be addressed at this stage to prevent inevitable future joint degeneration. The indications for joint fusion remain unclear and the tendency is to postpone this when possible until a later age. In recent years, arthroscopic resection of talocalcaneal coalitions has gained popularity, despite being technically demanding. It gives good visualization of the coalition, better postoperative pain relief and quicker improvement of the hindfoot stiffness.